2011
DOI: 10.1007/s10695-011-9519-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Haematococcus pluvialis supplementation on antioxidant system and metabolism in rainbow trout (Oncorhynchus mykiss)

Abstract: Effects of commercial source for astaxanthin (Haematococcus pluvialis) (H.p) on antioxidant power, specific marker enzymes, and some metabolites were examined in rainbow trout (Oncorhynchus mykiss). Fish were fed on diets containing 1, 3, and 10 g microalga kg(-1) feed for 30 days. Serum total antioxidant activity and lipid peroxidation product, indicated by malondialdehyde (MDA), significantly enhanced with different doses of administration, indicating the elevated antioxidant status in all treatment groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
87
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(100 citation statements)
references
References 27 publications
(30 reference statements)
12
87
1
Order By: Relevance
“…GOT and GPT are quantitatively the most important aminotransferases in fish. Both enzymes are extensively investigated in fish stress and health studies, and are commonly recognized as a valuable tool for indications of tissue damage [18,53]. In the present study, the lowest plasma GOT and GPT activities were both found in fish fed a CHO:L ratio of 5.64.…”
Section: Discussionsupporting
confidence: 48%
“…GOT and GPT are quantitatively the most important aminotransferases in fish. Both enzymes are extensively investigated in fish stress and health studies, and are commonly recognized as a valuable tool for indications of tissue damage [18,53]. In the present study, the lowest plasma GOT and GPT activities were both found in fish fed a CHO:L ratio of 5.64.…”
Section: Discussionsupporting
confidence: 48%
“…ALT and AST are commonly known as the crucial amino transferases in fish and normally are used as helpful indicators of liver damage in fish health studies (Hemre et al 1996;Sheikhzadeh et al 2012;Rao 2006;Wang et al 2014). D15 led to significant higher ALT activity compared to other groups, and 15 % dietary lipid seemed to do more harm to liver than the control diet do in our study.…”
Section: Discussionmentioning
confidence: 45%
“…High supplementation of dietary antioxidant caused a reduced need for the endogenous antioxidant enzyme (such as catalase and superoxide dismutase) in scavenging hydrogen peroxide (H 2 O 2 ) and superoxide radical (Lygren et al 1999). In accordance with the study by Sheikhzadeh et al (2012) and Da Silva et al (2015), supplementation of the high astaxanthin H. pluvialis into feed also leads to better performance with increased antioxidant activity in juvenile L. vannamei.…”
Section: Effect Of T Chuii As Feed Additives On Physical and Chemicasupporting
confidence: 62%